(untitled) (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
A reliability sensitivity analysis method based on linear moments (L-moments) is proposed in this paper to investigate the sensitivity of the failure probability to the correlation coefficients between input random variables. The sensitivity index is defined as the partial derivative of the failure probability with respect to the correlation coefficients that define the dependence structure among the inputs. A complete expression for the correlation sensitivity index is derived using the first four L-moments. As a by-product of the L-moments-based reliability analysis, the proposed method efficiently evaluates sensitivity information without requiring additional costly structural analyses. The effectiveness of the proposed method is demonstrated through a numerical example. The results show excellent agreement with those obtained from Monte Carlo simulation confirming the accuracy of the method.